Exercise training modalities in prediabetes: a systematic review and network meta-analysis - Zhang, Hang; Guo, Yuting; Hua, Guangshun; Guo, Chenyang; Gong, Simiao; Li, Min; Yang, Yan (Frontiers in Endocrinology, 2024)
In this network meta-analysis, we report that for prediabetes, moderate-intensity aerobic exercise combined with low-to moderate-load resistance training, moderate-intensity aerobic exercise, and low-to moderate-load resistance training should be considered the top three exercise interventions for improving glycemic control, weight control, and cardiovascular risk factors. Specifically, moderate-intensity aerobic exercise combined with low-to moderate-load resistance training showed the best results in reducing glycosylated hemoglobin (HbA1c), body mass index (BMI), body weight (BW), total cholesterol (TC) and low-density lipoprotein cholesterol (LDL); and low-to moderate-load resistance training was more effective at improving fasting blood glucose (FBG) than moderate-intensity aerobic exercise combined with low-to moderate-load resistance training. In addition, vigorous-intensity aerobic exercise significantly reduced systolic blood pressure (SBP) and 2-hour post-meal blood glucose (2hPG).In the subgroup analysis, we found that FBG reduction was more significant in patients older than 60. Moreover, improvements in HbA1c, TC and BMI increased with training time, but the optimal intensity and type of exercise remained moderate-intensity aerobic exercise combined with low-to moderate-intensity resistance training.